2021
DOI: 10.1021/jacsau.1c00082
|View full text |Cite
|
Sign up to set email alerts
|

From Chemical Curiosities and Trophy Molecules to Uranium-Based Catalysis: Developments for Uranium Catalysis as a New Facet in Molecular Uranium Chemistry

Abstract: Catalysis remains one of the final frontiers in molecular uranium chemistry. Depleted uranium is mildly radioactive, continuously generated in large quantities from the production and consumption of nuclear fuels and accessible through the regeneration of “uranium waste”. Organometallic complexes of uranium possess a number of properties that are appealing for applications in homogeneous catalysis. Uranium exists in a wide range of oxidation states, and its large ionic radii support chelating ligands with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…Examples of catalytic reactions mediated by uranium complexes have appeared in recent decades. [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] For example, Meyer and coworkers reported an example of uranium-mediated electrocatalytic production of H 2 from H 2 O. 76,77 Recently, Arnold and coworkers demonstrated that a dinuclear uranium complex could bind N 2 , mediating its reduction and functionalization to NH 3 .…”
Section: Articlementioning
confidence: 99%
“…Examples of catalytic reactions mediated by uranium complexes have appeared in recent decades. [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] For example, Meyer and coworkers reported an example of uranium-mediated electrocatalytic production of H 2 from H 2 O. 76,77 Recently, Arnold and coworkers demonstrated that a dinuclear uranium complex could bind N 2 , mediating its reduction and functionalization to NH 3 .…”
Section: Articlementioning
confidence: 99%
“…54 These results represent the first example of alkyne hydroboration catalyzed by a multimetallic U−Co species. 55…”
Section: Small-molecule Activation and Catalysismentioning
confidence: 99%
“…Progress has ranged from the discovery of new oxidation states (An 2+ ; An = Th, U, Np, Pu) 13,[17][18][19]23,24 to an array of non-actinyl multiple-bond chemistry, 1−3,25−32 to covalency studies 4,9,26,33−36 and small molecule reactivity. 15,37,38 An expanding and diverse synthetic "toolbox" of nonaqueous, organic solvent soluble Th/U starting materials has been key in facilitating the explosion of molecular chemistry studies for these early actinide elements. Addressing the documented limitation of U 3+ starting materials, 39 in the late 1980s and mid-1990s, facile routes were reported to [UI 3 (THF) 4 ] (THF = tetrahydrofuran), [UI 3 (DME) 2 ] (DME = 1,2-dimethoxyethane), [UI 3 (py) 4 ] (py = pyridine), and [UBr 3 (THF) 4 ], through oxidation of amalgamated uranium metal turnings with I 2 or Br 2 in Lewis base solvents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The scientific understanding of the role that f-electrons play in the bonding, electronic structure, redox chemistry, and physics of the actinides (An) is continually evolving. ,, Widespread advances over the last 30 years have remapped the known boundaries of molecular Th and, in particular, U molecular chemistry. Progress has ranged from the discovery of new oxidation states (An 2+ ; An = Th, U, Np, Pu) , ,, to an array of non-actinyl multiple-bond chemistry, , to covalency studies ,,, and small molecule reactivity. ,, An expanding and diverse synthetic “toolbox” of nonaqueous, organic solvent soluble Th/U starting materials has been key in facilitating the explosion of molecular chemistry studies for these early actinide elements. Addressing the documented limitation of U 3+ starting materials, in the late 1980s and mid-1990s, facile routes were reported to [UI 3 (THF) 4 ] (THF = tetrahydrofuran), [UI 3 (DME) 2 ] (DME = 1,2-dimethoxyethane), [UI 3 (py) 4 ] (py = pyridine), and [UBr 3 (THF) 4 ], through oxidation of amalgamated uranium metal turnings with I 2 or Br 2 in Lewis base solvents. , This route to [UI 3 (THF) 4 ] (and other Lewis base adducts) as well as the synthesis of [U­(N″) 3 ] (N″ = {N­(SiMe 3 ) 2 }) generated from these halide complexes (which was more convenient than prior routes to [U­(N″) 3 ], which comprised the in situ reduction of UCl 4 with Na/(C 10 H 8 ) and then reaction with NaN″), has become a staple of U chemistry. , Building upon those contributions, additional precursors and routes to U 3+ and U 4+ synthons have been established using U 0 metal as the source material and also metallic-phase-free routes.…”
Section: Introductionmentioning
confidence: 99%